Efeitos do treinamento concorrente em parâmetros bioquímicos, cardiovasculares, neuromusculares e de composição corporal em idosas - Campos, Anderson Leandro Peres (2012)
Training programs that include aerobics and strength exercises, either at the same session or alternate days have been defined as concurrent training. The objective of this study was to verify the effects of a concurrent training on biochemical parameters, cardiovascular fitness, body composition and neuromuscular aspects in elderly women and to compare them to the effects of strength and aerobics programs exclusively. Twenty two elderly women physically active were randomly allocated to one of the five groups: AS (aerobic exercises followed by strength training N=5), SA (strength activities followed by aerobics exercises N=5), AG (aerobics exercise only N=5), SG (strength activities only N=4), CG (control group N=3). In the aerobics power test, AS and SA groups showed differences in the pos-test compared to the CG (p=0.001 and 0.04). In dynamic strength test of upper limbs, the groups S, SA, AS showed statistical differences from the CG in the pos-test (p=0.009, 0.006 and 0.002 respectively). Only the AS group presented some difference from the pre to pos tests (P=003). AG, SG, SA, AS showed statistical differences in the post test in relation to the CG for the lower limbs strength test (p<0.001). From pre to post test within the same group, the groups SG, SA and AS showed statistical differences (p=0.001, 0.03, 0.02). Stretching, static strength, biochemical factors and body composition showed no association with any of the groups. It was concluded that in these elderly women, the concurrent training was equivalent to the strength and aerobics exercises performed exclusively.